Exploring Communication Dynamics in Organizational Leadership and Work Behavior: A Case Study of SEMA FITK UIN Sunan Kalijaga - Diah Khoirohnisah; Khayyun Latifah; Rina Khaerunnisa; Syaras Luthfiasari (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – This study aims to delve into the intricate relationship between communication, leadership, and work behavior within the Faculty of Tarbiyah and Teacher Training (FITK) at UIN Sunan Kalijaga, focusing on the Student Executive Board (SEMA). Design/methods/approach – Employing a qualitative descriptive research design, the study utilized primary data from interviews with key SEMA figures and observational techniques, supplemented by extensive library research for secondary data. This approach facilitated a comprehensive understanding of the communication dynamics within SEMA FITK. Findings – The research revealed that effective communication is pivotal in guiding, motivating, and enhancing organizational performance and human resource management. Leadership within the organizational culture, communication patterns, and their interconnectedness with work behavior emerged as key factors influencing organizational success. Research implications/limitations – The findings contribute to existing literature on organizational communication, leadership, and work behavior. However, the study is limited by its specific focus and reliance on secondary data. Future research should include diverse organizational types and investigate digital communication tools. Practical implications – The study highlights the importance of integrating effective communication strategies in organizational management and human resource practices to foster a positive culture and enhance performance. Originality/value – This research underscores the critical role of communication in organizational contexts, illustrating its complex interplay with leadership and work behavior. It provides valuable insights for both theoretical and practical applications in organizational management.